Assessment of current status of women farmers in Japan using empowerment indicators (2007)
This research assessed the current status of Japanese women farmers using universal measurement of women empowerment. Two prefectures, Hiroshima and Shimane were selected. Stratified sampling technique was used to select respondents from each village while structured questionnaire was employed to collect data on economic, social, familial, legal, mobility and political status of the respondents. The result shows that status of women farmers was improved in the recent time compared to years back. This was revealed in the favourable responses to some statement questions such as; freedom and participation in voting, relationship with husband, participation in outside work and freedom of movement. However, their status as unpaid workers on family farms, lack of freedom to borrow and lend, inability to express their mind over the children to mother-in- law were the prevailing items of their disempowerment. Classifying respondents on the overall empowerment shows that majority of them were highly empowered. Inferential analysis using t-test to compare women farmers past and present status shows a significant difference, t = 4.827, p = 0.000. Relationship between personal characteristics of women farmers and their present empowerment status using Pearson Product Moment Correlation (PPMC) coefficient r shows negative correlation between age and all empowerment indicators. Also marital status has negative correlation with familial and legal empowerment while mother-in-law and familial empowerment were positively correlated. It therefore suggests that status of women farmer in Japan has improved, compare to their situation years back.